Destruction of Lysozyme Amyloid Fibrils Induced by Magnetoferritin and Reconstructed Ferritin - Gombos, Jan; Balejcikova, Lucia; Kopcansky, Peter; Batkova, Marianna; Siposova, Katarina; Kovac, Jozef; Zolochevska, Kristina; Safarik, Ivo; Lokajova, Alica; Garamus, Vasil M; Dobrota, Dusan; Strbak, Oliver (International journal of molecular sciences, 2022)
Neurodegenerative disorders, including Alzheimer's disease (AD), Parkinson's disease (PD), or systemic amyloidosis, are characterized by the specific protein transformation from the native state to stable insoluble deposits, e.g., amyloid plaques. The design of potential therapeutic agents and drugs focuses on the destabilization of the bonds in their beta-rich structures. Surprisingly, ferritin derivatives have recently been proposed to destabilize fibril structures. Using atomic force microscopy (AFM) and fluorescence spectrophotometry, we confirmed the destructive effect of reconstructed ferritin (RF) and magnetoferritin (MF) on lysosome amyloid fibrils (LAF). The presence of iron was shown to be the main factor responsible for the destruction of LAF. Moreover, we found that the interaction of RF and MF with LAF caused a significant increase in the release of potentially harmful ferrous ions. Zeta potential and UV spectroscopic measurements of LAF and ferritin derivative mixtures revealed a considerable difference in RF compared to MF. Our results contribute to a better understanding of the mechanism of fibril destabilization by ferritin-like proteins. From this point of view, ferritin derivatives seem to have a dual effect: therapeutic (fibril destruction) and adverse (oxidative stress initiated by increased Fe2+ release). Thus, ferritins may play a significant role in various future biomedical applications.
Keywords: Ferritins; Muramidase; muramidasa; Amyloid; ferritiny; železo; amyloid; Iron